South African Propaganda Agencies and the Battle for Public Opinion during the Second World War, 1939–1945 - Monama, Fankie L. (Scientia Militaria - South African Journal of Military Studies, 2016)
South Africa’s entry into the Second World War in 1939 was complex. The Smuts government lacked nation-wide support and experienced hostile reactions from opponents of its war policy. It was also subjected to Nazi propaganda offensives, which intensified national divisions and undermined public morale. In response, the Union authorities adopted a volunteer policy for military service and embarked on a massive drive to secure positive public opinion and national support for the war policy. This move led to the establishment of various publicity and propaganda organisations to influence public opinion and to stimulate enthusiasm for the war. However, inadequate policy direction and lacking a solid framework to guide propaganda organisation and operations created inter-agency frictions and rivalries. The study on which this article is based, examined the main propaganda agencies, the Bureau of Information (BOI), the Directorate of Military Intelligence (DMI) and the Union Unity Truth Service (UUTS), which contested one another for jurisdiction, authority and power to shape public opinion in South Africa during the war. The analysis focused on the rationale for their establishment, their purpose, objectives and activities. Then the article reports on the inter-institutional relationships, organisational politics and competition, and how these aspects affected the Union’s propaganda enterprise, mobilisation drive and the prosecution of the war effort.